2015
DOI: 10.1039/c4cp04137b
|View full text |Cite
|
Sign up to set email alerts
|

Water transport in the nano-pore of the calcium silicate phase: reactivity, structure and dynamics

Abstract: Reactive force field molecular dynamics was utilized to simulate the reactivity, structure and dynamics of water molecules confined in calcium-silicate-hydrate (C-S-H) nano-pores of 4.5 nm width. Due to the highly reactive C-S-H surface, hydrolytic reactions occur in the solid-liquid interfacial zone, and partially surface adsorbed water molecules transforming into the Si-OH and Ca-OH groups are strongly embedded in the C-S-H structure. Due to the electronic charge difference, the silicate and calcium hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Therefore, LPMSC-1 and LPMSC-2 could bind rhPDGF-BB via hydrogen bonds. [26][27][28][29] However, there was no Si-OH on the surface because LPMSC-3 was completely transformed…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LPMSC-1 and LPMSC-2 could bind rhPDGF-BB via hydrogen bonds. [26][27][28][29] However, there was no Si-OH on the surface because LPMSC-3 was completely transformed…”
Section: Discussionmentioning
confidence: 99%
“…In the work of Hou et al [68], it is shown that a C-S-H surface is highly reactive, and hydrolytic reactions occur in the solid-liquid interfacial zone. They explain that a part of the adsorbed water molecules transforms into the Si-OH and Ca-OH groups.…”
Section: Surface Analysismentioning
confidence: 98%
“…At 5 Å, the shear strenght has dropped to as much as 10% of the ideal contact case, and the system loses all the cohesion under shear strain at 1 nm separation. It is interesting to note that for such a small distance the water is considered to present confined dynamics, with lower mobility than bulk water (Bonnaud et al 2010;Hou et al 2015). However, in terms Rev.…”
Section: Figure 2 Stress-strain Curves For the Ideal Contact Interfamentioning
confidence: 99%